2015
DOI: 10.1007/s40948-015-0005-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical properties of Bundelkhand granite near Jhansi, India

Abstract: Creation of optimal fracture networks through enhanced geothermal system within the reservoir for the extraction of the geothermal energy will require proper understanding of the thermo-mechanical behavior of the reservoir rocks i.e. granites. Current research work has focused the thermo-mechanical properties of granite under various temperature and strain rate conditions. Bundelkhand granite of India has been investigated for the proposed research work. Four different strain rates viz. 0.05, 0.5, 5.0 and 50.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The main reason for the losses in elastic and strength properties was a dense fracture network, which was an outcome of the high-temperature treatment. The article [47] confirmed that the thermally induced fracture network is a major source of weakening of the TT granite mechanical properties (Figure 24). The hydraulic fracturing experiments were monitored by a combination of independent systems, such as AE monitoring and pressure, volume and deformation sensors.…”
Section: Discussionsupporting
confidence: 54%
“…The main reason for the losses in elastic and strength properties was a dense fracture network, which was an outcome of the high-temperature treatment. The article [47] confirmed that the thermally induced fracture network is a major source of weakening of the TT granite mechanical properties (Figure 24). The hydraulic fracturing experiments were monitored by a combination of independent systems, such as AE monitoring and pressure, volume and deformation sensors.…”
Section: Discussionsupporting
confidence: 54%
“…Some researchers investigated changes in physical properties such as mass, volume, density, unit volume weight, P and S wave velocity, porosity, and permeability and mechanical properties such as compressive strength, point load strength and elastic modulus values after slow (air) cooling from high temperature. Singh et al (2015) have focused on impacts on the thermal and mechanical properties under different temperature of Bundelkhand granite of India. They noticed that the young's modulus reduces with an increase in temperature of granite.…”
Section: Previous Studiesmentioning
confidence: 99%
“…While, the high temperature and pressure of water hydro-thermal influences on gritstone are few investigated, especially the coupled hydro-thermal effect on physical and mechanical properties of gritstone. However, in recent years, the behavior of rocks under thermos-mechanical coupling (TM) and measurement of basic physical and mechanical parameters is very complex (Hudson et al, 2009;Dutt et al, 2012;Bonte et al, 2014;Sengun, 2014;Singh et al, 2015;Shi et al, 2018;Wang and Konietzky, 2019). It includes rock deformation modulus, Poisson's ratio, tensile strength, compressive strength, cohesion, internal friction Angle, viscosity, thermal expansion coefficient and other changes with temperature (Gautam et al, 2016;Guha Roy and Singh, 2016;Yao et al, 2016;Sirdesai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%